Modulação do processo cicatricial de feridas cutâneas experimentais por uma biomembrana de proteínas do látex de Calotropis procera (AIT.) R. Br. - Figueiredo, Ingrid Samantha Tavares de (2011)
The latex of the medicinal plant Calotropis procera (Apocynaceae) is a complex chemical, consisting of a variety of molecules and has been widely used in folk medicine on skin diseases. The potential of the latex proteins fraction (LP) in induce cell damage was assessed by MTT and LDH tests. Moreover, LP was used to prepare a biomembrana associated with poly (vinyl alcohol) (BioMem PVA/PL 0,2% and 1%).The physical-chemical properties of control (PVA 1%) and test (BioMem PVA/PL 1%) were assessed by infrared spectroscopy (FTIR) and thermogravimetric (TGA) analysis. The effect of laticifers proteins at healing was investigated after induction of incision or excision wounds on the back of mices, followed by implantation of BioMem PVA/PL 0,2% or 1%. Healing process was evaluated by the parameters: macroscopic analyses (induction of tissue neoformation of incisional wounds and edema, hyperemia, area reduction and re-epithelialization of excision wounds); microscopic (mast cell degranulation, edema, leucocyte infiltrate, number of fibroblasts and collagenesis). Inflammatory markers and mediators (MPO, nitrite, IL-1β e TNF-α) were evaluated in incision and excision wounds. Microvessel density was evaluated in incision wounds. The possible effect of soluble protein fraction (LP) to directly stimulate macrophages was investigated in a cell culture. PL shows no cytotoxicity in vitro in human neutrophils, since the low activity of LDH and high vibility of neutrophils by MTT test. The physico-chemical analysis showed that no strong interaction with PVA and LP occurred, since was not observed the formation of new bands or the displacement of these. Futhermore, the solubility of these compounds became the BioMem PVA/PL more thermally stable. At experimental healing models, macroscopic analyses showed that BioMem PVA/PL 0,2% e 1% leads tissue neoformation in incisional wounds at the 2, 7 and 14 days after membrane implantation. However, no effect on the microvascular density to neoformed tisse of incisional wounds were seen. At excisional wounds, BioMem PVA/PL 0,2% induce increase of edema, but not hyperemia at inflammatory phase. Moreover, accelerated the reduction in the wound area and an improved re-epithelialization at proliferative phase of wound healing. Microscopic analysis of incisional and excisional wounds showed that BioMem PVA/PL 0,2% or 1% lead a stimulus to mast cell degranulation, edema, leucocyte migration at inflammatory phase of the cicatricial process. At the proliferative phase, was evidenced an increase in the population of fibroblasts and collagenesis. Re-epithelialization of excisional wounds showed an increased thickness of the newly formed epithelium. BioMem PVA/PL 0,2% implantation increased the levels of markers and mediators of the inflammatory response, such as MPO, nitrite, IL-1β and TNF-α. Culture mouse macrophages stimulated with PL were induced to release of TNF- e IL-1β. Integrated analysis of all results suggest that PL act significantly in the inflammatory phase of healing, which seems to directly influence the subsequent phases of the healing process.